Generalized Beamspace Modulation Using Multiplexing: A Breakthrough in mmWave MIMO - Guo, Shuaishuai; Zhang, Haixia; Zhang, Peng; Zhao, Pengjie; Wang, Leiyu; Alouini, Mohamed-Slim (IEEE journal on selected areas in communications, 2019)
This paper proposes a generalized beamspace modulation using multiplexing (GBMM) scheme for millimeter wave (mmWave) multiple-input multiple-output (MIMO) communications with reduced radio frequency (RF) chains. Besides achieving a multiplexing gain over the selected beamspace set, GBMM additionally makes use of the index of the beamspace set to carry information. In the proposed GBMM, the beamspace sets are non-uniformly activated. We investigate the spectral efficiency (SE) of the proposed GBMM and the SE-oriented beamspace set activation probability optimization as well as the hybrid precoder design. In the hybrid precoder design procedure, we first design the fully-digital precoders and then adopt the optimized fully-digital precoders to design the hybrid precoders. A gradient ascent algorithm is developed to find the optimal fully-digital precoders and precoder activation probabilities. In the high signal-to-noise-ratio (SNR) regime, closed-form solutions of the fully-digital precoders and the precoder activation probabilities are derived. Moreover, we investigate the impact of the hybrid receiver structure on the performance of GBMM, propose a coding method to realize the optimized precoder activation, and discuss the extension to orthogonal frequency division multiplexing (OFDM)-based mmWave broadband communications. Both analytical and numerical results show that GBMM outperforms the spatial multiplexing over the best beamspace set in terms of SE, which has been well recognized as the best transmission solution in mmWave MIMO communications.